Production of Cloned Asian Elephant Embryos Using an Interspecies Somatic Cell Nuclear Transfer (iSCNT) Technique - Anucha Sathanawongs,; Yada Jarujinda,; Suvichai Rojanasthien,; Apichart Oranratnachai, (Agriculture and Natural Resources, 2010)
This study was carried out to investigate the feasibility of using interspecies somatic cell nuclear transfer (iSCNT) techniques in Asian elephants (Elephas maximus), using elephant fibroblasts as donor cells and rabbit oocytes as the recipient cytoplasts. Elephant fibroblasts were collected post-mortem from the ear skin of a female Asian elephant and cultured in vitro. Monolayer fibroblasts were trypsinized and used for SCNT. The comparative study showed that the blastocyst rates from iSCNT were significantly lower (P<0.05) than for rabbit SCNT and rabbit parthenogenesis (19.4, 56.7, and 70.3%, respectively). The study tried to improve the efficiency of iSCNT by using phytohemagglutinin-P (PHA-P) to increase the fusion rate and nocodazole to synchronize donor cells in the G1 stage of the cell cycle. The fusion rate of elephant-rabbit couples treated with PHA-P was significantly increased (47.5%) compared with the non-treated group (26.2%; P<0.05). The cloned embryos could develop into blastocysts (27.8%), which was significantly (P<0.05) higher than for the non-treated cells group (14.4%). By using this protocol, Asian elephant blastocysts can be produced by iSCNT of fibroblast cells into rabbit cytoplasts with the use of nocodazole and PHA-P. The blastocyst rate of cloned elephant embryos using rabbit cytoplasts was more than 25% and may have potential in further studies on elephant preservation.